2010
DOI: 10.1186/1476-511x-9-137
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary cold-pressed turnip rapeseed oil and butter on serum lipids, oxidized LDL and arterial elasticity in men with metabolic syndrome

Abstract: BackgroundRapeseed oil is the principal dietary source of monounsaturated and n-3 polyunsaturated fatty acids in the Northern Europe. However, the effect of rapeseed oil on the markers of subclinical atherosclerosis is not known. The purpose of this study was to compare the effects of dietary intake of cold-pressed turnip rapeseed oil (CPTRO) and butter on serum lipids, oxidized LDL and arterial elasticity in men with metabolic syndrome.MethodsThirty-seven men with metabolic syndrome completed an open and bala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 51 publications
1
26
0
Order By: Relevance
“…Five of the seven studies examined the effects of margarines or mayonnaises made with canola oil on TC levels and all showed a lowering of TC levels, in a range from 3.3% to 21.7%, compared with a high‐SFA‐treated group. Palomäki et al . and Valsta et al .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five of the seven studies examined the effects of margarines or mayonnaises made with canola oil on TC levels and all showed a lowering of TC levels, in a range from 3.3% to 21.7%, compared with a high‐SFA‐treated group. Palomäki et al . and Valsta et al .…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies compared canola oil‐based diets with those high in SFAs . The high‐SFA diets in these studies contained >12% of energy from SFAs and >30% of energy from total fat, mainly in the form of butter, margarine, mayonnaise, and other high‐SFA foods.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is assumed that physical activity has a positive effect on reducing the risks of changing factors like blood pressure, serum lipid profile, glucose tolerance and obesity. It is believed that the best result among those with higher energy consumption of 2000 calories per week of physical activity, which represents about 1 hour of daily exercise (14). The results of our study showed that the highest percentage (38.4%) patients a day to walk 15-30 minutes, 24.2% of respondents could not walk, and the lowest percentage (4.5%) patients a day hike of more than one hour.…”
Section: Discussionmentioning
confidence: 60%